SURGICAL MANAGEMENT OF DYSTOCIA IN A RAJAPALAYAM DOG DUE TO PRIMARY UTERINE INERTIA - M MURALI, REVATHY; M HARSHAN, HIRON; V K, VIDYA; PRATHAP, GAYATHRI; BABU, ANILA; BIRADAR, VINAYAK (The Indian Journal of Animal Reproduction, 2022)
A three year old primiparous female Rajapalayambitchcrossed 63 days back was presented to the TeachingVeterinary Clinical Complex (TVCC), Mannuthy, with a complaint of difficulty in whelping. Per vaginal examinationrevealed a foetus in the birth canal and bitchdid not exhibit any signs of uterine contractions and straining. Sonographicexamination revealed viable foetuses with low heart beats. The foetus presented was expelled, following medicalmanagementwithout any assistance and no further progress was observed. Remaining seven live pups present in thedistended and extremely thin uteruswere recovered by conducting emergency caesarean section. The condition wasclinically diagnosed as partial primary uterine inertia due to over distension of the gravid uterus.
Keywords: Rajapalayam; partial primary uterine inertia; caesarean-section